Enfermedad de Kawasaki: un caso con pseudo-obstrucción intestinal y aneurisma gigante - Tori Tori, Carlos; Vargas Galgani, Mario (Revista Médica Herediana, 2015)
We present a rare association of Kawasaki disease in a two year old boy presenting with fever, a morbiliform rash and clinical signs of intestinal pseudo-obstruction. Our patient subsequently developed a giant aneurysm of the right coronary artery complicated with thrombosis. He presented fever again 48 hours after the first dose of Immunoglobulin and needed a second one with good results. These patients with giant coronary aneurysms have a greater risk of developing stenosis and myocardial infarction, and require anticoagulant therapy, frequent stress scans and coronary angiographies. Those who developed less severe disease need only antiplatelet therapy and less frequent cardiovascular tests. Patients with a normal echocardiogram after the acute phase of the disease are not treated. The long-term prognosis of this disease is uncertain, especially regarding the possible association with coronary disease in adult life.